People and things in the ethnography of borders: materialising the division of Sarajevo. (6th February 2013) - Jansen, Stef
Abstract : This article addresses the contrasting pull of two tendencies in anthropology: (a) calls to redress the purification of human from non‐human actants and (b) calls to denaturalise notions of borders as things, foregrounding borderwork. The resulting dilemma – do we treat people and things as equivalent actants on a 'flat' plane or not?– is explored through an ethnographic exercise on the border that divides Sarajevo. This case study crystallises methodological possibilities, implications for critique and matters of accountability presented by either path. Ultimately, I argue, a focus on things is productive insofar as it functions within a focus on human practice.